(untitled) (Environment & Health, 2023)
Comparative analysis showed that in the subgroup of girls with overweight, the proportion of cases of carriage of genotypes composed of neutral alleles of the C/C polymorphism MTHFR:677 is greater than in the subgroup of harmoniously developed girls. At the same time, a lower specific activity of 137Cs in their body was registered. It is concluded that incorporated 137Cs radionuclides cause a decrease in body weight in children living in the area affected by the accident at the Chоrnobyl nuclear power plant. At the same time, there is a metabolic disorder, in the form of an increase in the content of Hcy in the blood, more pronounced in boys. The process of incorporation of 137Cs radionuclides into the body of children may be associated with the T allele of the MTHFR:C677 polymorphism, which affects the activity of methylenetetrahydrofolate reductase.